2011
DOI: 10.1128/jcm.02299-10
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Transmission of Mycobacterium bovis in the United Kingdom in 2005 to 2008

Abstract: Due to an increase in bovine tuberculosis in cattle in the United Kingdom, we investigated the characteristics of Mycobacterium bovis infection in humans and assessed whether extensive transmission of M. bovis between humans has occurred. A cross-sectional study linking demographic, clinical, and DNA fingerprinting (using 15-locus mycobacterial interspersed repetitive-unit-variable-number tandem-repeat [MIRU-VNTR] typing) data on cases reported between 2005 and 2008 was undertaken. A total of 129 cases of M. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
1
11
1
1
Order By: Relevance
“…We identified, unlike previous studies ( 4 , 5 ), that although the number of M. bovis patients not born in the United Kingdom remained low and fluctuated over time, the annual number of cases in this group increased slightly over time. Our finding may be confounded by better recording of place of birth but is not unexpected given the increase during this period in the overall number of TB patients not born in the United Kingdom ( 13 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We identified, unlike previous studies ( 4 , 5 ), that although the number of M. bovis patients not born in the United Kingdom remained low and fluctuated over time, the annual number of cases in this group increased slightly over time. Our finding may be confounded by better recording of place of birth but is not unexpected given the increase during this period in the overall number of TB patients not born in the United Kingdom ( 13 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding may be confounded by better recording of place of birth but is not unexpected given the increase during this period in the overall number of TB patients not born in the United Kingdom ( 13 ). Similar to previous findings ( 5 ), our findings indicate that most M. bovis patients not born in the United Kingdom lived in urban areas, specifically London. These patients originated mostly from low-income countries where TB incidence is high and therefore are at higher risk for human-to-human transmission and animal-to-human transmission because of limited detection of M. bovis in animals and less frequent milk pasteurization ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…Zoonotic tuberculosis, which is caused by the bacteria Mycobacterium bovis is typically passed on by consumption of unpasteurised dairy products, but also by blood contact or droplet transmission. It predominately causes tuberculosis in cattle and is the causative organism in <0.5% of culture-confirmed tuberculosis in the UK 3. It manifests almost identically to M. tuberculosis infection, and although pulmonary tuberculosis remains the most common presentation, extrapulmonary disease is more frequent, particularly involvement of the gastrointestinal system 4.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported on M. bovis [19,20]. In the UK and the Netherlands the number of M. bovis cases is low compared to the number of M. tuberculosis cases.…”
Section: Surveillance Reportsmentioning
confidence: 99%
“…The studies reporting surveillance data are summarised in table 2 [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Surveillance Reportsmentioning
confidence: 99%